PENEGAKAN DISIPLIN PELAKU PELANGGARAN KODE ETIK KEPOLISIAN NASIONAL TIMUR LESTE SEBAGAI WUJUD PEMBINAAN APARATUR KEPOLISIAN NEGARA YANG TAAT HUKUM - Sabino Freitas; Seguito Monteiro; Jose Agostinho D.B.P; Elly Kristiani Purwendah (Program Studi Ilmu Hukum, Jurusan Hukum dan Kewarganegaraan, Fakultas Hukum dan Ilmu Sosial, Universitas Pendidikan Ganesha, 2024)
The enforcement of law carried out by the National Police of Timor-Leste in performing its state duties encompasses maintaining public security and order as a form of providing protection, guidance, and service to the community. This research aims to identify the factors causing members of the National Police of Timor-Leste in Baucau Municipality to abandon their duties and violate the code of ethics. The study employs an empirical juridical approach. The findings indicate that the application of sanctions for violations of the code of ethics within the National Police of Timor-Leste is based on prevailing laws and regulations. Over five years, punishments included verbal reprimands for 32 officers, written reprimands for 21 officers, and suspension from duty for 12 officers.